Effect of Li2O on rheological properties, structure, and crystallization of mould flux for high-speed thin-slab continuous casting. (7th February 2022) - Yuan, Zhipeng; Zhu, Liguang
ABSTRACT: The effects of Li2 O content on the rheological properties, melt structure, and crystallization behaviour of mould flux for high-speed thin slabs are systematically studied. The results show that when the Li2 O content increases from 0.86% to 5.81%, the viscosity of the mould flux decreases, the melting range increases, and the break temperature initially decreases followed by an increase. Further study shows that Li2 O can release O 2− and depolymerize complex Si–O–Si and Al–O–Al structural units into Si–O and Al–O structures. Simultaneously, Li2 O can compensate for the charge between Si 4+ and Al 3+ by providing Li + in combination with the mould-flux network structure, making the Si–O–Al structure unit more stable. With the increase in Li2 O content in the slag, the crystallization of the mould flux is inhibited at first, and subsequently, it is enhanced. When the Li2 O content is 4.33%, the precipitation of Lithium metaaluminate enhances the crystallization behaviour of the mould flux.